A study on the current promotional strategies of Guthrie Aviation Services Sdn. Bhd. (GASSB) helicopter services / Fariz Abdul Aziz - Abdul Aziz, Fariz (1995)
Helicopter charter business has been positive for the past few years in Malaysia . However, this potential business is still new and alien to the general public. Being one of the pioneers in this business, Guthrie Aviation Services Sdn. Bhd. (GASSB) faces several problems like any other local helicopter companies. It is due to the rising cost of spare parts, import duties and helicopter fuel and oil as well as maintenance. Since there are many new entries into this industry, another problem arises in GASSB services is the marketing aspect. This study has discovered that lack of proper promotion and limited information given to the general public on GASSB services as well as ineffective market segmentation have an unpleasant impact on the service too. Due to these factors and the problems associated with them, a study was carried out to determine and identify GASSB promotional strategies and market segmentation through research and observation. This was followed by the application of effective marketing theory and giving recommendation based on observation and research findings.